Utilization of green ATR-FTIR spectroscopic method for quantitative analysis of Ibuprofen tablets - Khairi M. S. Fahelelbom; Abdullah Saleh; Ramez Mansour; Rami Abujarad (Pensoft Publishers, 2023)
Aim: The aim of this study is to propose a green and nondestructive method using the ATR-FTIR method for the quantitative analysis of Ibuprofen tablet dosage forms. Herein, the technique has been validated as an alternative green tool that evades necessary sample preparation procedures required in traditional quantitative methods. Methods: The method depends on selecting CO of the Ibuprofen stretching band in the range 1620-1750 cm-1 to quantitatively determine Ibuprofen in original samples. The pack area (AUC) from ATR-FTIR spectral scanning of samples has been determined through the first derivative measurements. Results: The assay results indicated that no interferences between the excipients or additives and the active ingredients of the commercial tablets interferences. The linearity is excellent within the concentration range of 0.2 to 1.5 w/w % (r = 0.9994). A percentage of recoveries ranged between 99.7-10.5 which are in good agreement with the pharmacopeial percent recovery standards. The high degree of sensitivity of the technique was demonstrated by obtaining a 0.028 w/w % detection limit and a 0.1599 w/w % limit of quantification values.